XANES study of electronic and structural nature of Mn-sites in manganese oxides with catalytic properties - Figueroa, Santiago Jose Alejandro (2005)
The characterization of a series of manganese oxides prepared by different methods were performed by X-ray diffraction (XRD) and X-ray absorption near-edge structure (XANES) analysis. Low crystallized phases were found by means of XRD. The XANES results indicated that the mean oxidation state value of all the samples was between 3+ and 4+. XANES analysis of spectra and extended X-ray absorption fine structure (EXAFS) data revealed that Mn was present in three different octahedral environments; one of them corresponded to the environment of Mn in the pyrolusite phase while the other two can be associated to Mn in ramsdellite-like environment and Mn in a octahedral site with Mn-vacancies in the second shell of coordination. The different oxides were analyzed in the reaction of total oxidation of ethanol and we found that the catalytic activity was enhanced when the couple Mn3+-Mn4+ was present in the structure of the oxides.